Effect of freezing period and defrosting methods on chemical composition and microbial count in beef cuts (Bangladesh Journal of Animal Science, 2014)
The experiment was conducted to examine the effect of freezing and defrosting methods on the quality of beef. Two types of beef samples named as fresh and cured beef samples were taken. Both types were divided into three sub divisions namely air, water and microwave oven. These samples were stored at -20°C temperature in the freezer for 90 days and analyzed on 10th, 45th and 90th day. The dry matter, crude protein, ether extract and ash percentages and standard plate count (SPC) were differed significantly (p